Analysis Of Students' Errors In Solving Mathematics Problems In Algebra Shape - Renata Kamagi; Sylvia J. A. Sumarauw; Ichdar Domu (Departement of Mathematics Education, 2023)
This study aims to describe the mistakes of class VII students of SMP Negeri 1 Tondano in solving questions on the Algebraic Forms material in the bold and alluring learning process. The errors referred to here may occur in solving Algebra Form problems, including principle and concept errors. The type of research used is descriptive research with a qualitative approach. Data collection techniques are carried out through tests, interviews, and documentation. The sources and subjects of this study were class VII students of SMP Negeri 1 Tondano T/A 2020/2021 and T/A 2022/2023, who were selected based on considerations. Data analysis techniques in this study are the stages of data reduction, data presentation, and conclusions. The results of this study indicate that the mistakes made by students are: 1) conceptual errors, where they cannot identify elements in the algebraic form, such as terms, variables, coefficients, and constants. 2) the principle of error, where it is wrong to operate algebraic forms that have negative terms, and errors in determining operations on terms that are not similar. The causal factors in brave learning are: 1) working on questions in a hurry; 2) do not understand the concept in Algebraic Forms; 3) do not know how to operate tribes that are not of the same type; 4) do not know the correct settlement calculation operating procedure; 5) not careful in working on the questions; 6) ambient distractions that make it out of focus. The causal factors in engaging learning are: 1) Class conditions are not conducive; 2) decreased student discipline.